The impact of maternal versus paternal imprisonment on their children’s health: A scoping review - Naomi Gadian; Abigail Dunn; Donna Arundel; Sara Morgan; Paula Harriott; Lucy Wainwright; Emma Plugge (PLoS ONE, 2025)
Background Rates of imprisonment for both women and men are high in England and Wales yet no official records report the number of people in prisons who are parents. Reports suggested 54% of people in prison have children under the age of 18 years which is estimated to affect 312,000 children annually. Research has examined the impact of parental imprisonment on their children, but little is known about the health and wellbeing outcomes for children who experience maternal versus paternal imprisonment. The Prison Reform Trust reported only 9% of children live with their father at the time of their mother’s incarceration, whilst 75% of children live with their mother at their father’s incarceration. The aim of this scoping review was to review the published evidence about the health impacts of maternal versus paternal imprisonment to enable a better understanding of the differential impacts on affected children and to identify where gaps in the evidence remain. Methods The Arksey and O’Malley methodology for scoping review was used to address how do the physical, mental and behavioural health, along with healthcare service use differ between children who experience their mother being imprisoned, compared to those who experience their father being imprisoned. Databases searched included Medline, Embase, CINAHL, Cochrane, PyschINFO, Web of Science, Delphis and IBBS. The search yielded 9,773 results, which after screening and removal of duplicates, resulted in 20 papers being included. Results All included papers compared data relating to outcomes for children who had experienced maternal or paternal imprisonment to children with no parental imprisonment, and three compared maternal to paternal imprisonment. Eighteen used populations in the United States of America and of these, thirteen used data from two studies. Having experienced either parent being in prison results in considerable impacts on the health of children, as well as their support networks and the stigma they encounter. The findings comprised of four main categories of health: physical health, mental health, behavioural health and healthcare service use. Discussion This review highlighted how atomised the study designs and study populations were in addition to the varied findings about the impact of maternal and paternal imprisonment on children. The sparsity of literature resulted in challenges addressing the original study question about how health and wellbeing outcomes differ for children experiencing maternal versus paternal imprisonment and no clear conclusions can be drawn. Conclusion There is limited understanding about the impact of maternal or paternal imprisonment on their children’s health and behaviour, despite the substantial implications their imprisonment has and the stigma. It is important to consider that the absence of clear significant findings, does not negate the great health needs for this cohort. Further research is vital to ensure this population is identified, recognised and supported appropriately.